Morphology and nanoindentation properties of mouthparts in Cyrtotrachelus longimanus (Coleoptera: curculionidae). Issue 7 (28th February 2017) - Li, Longhai; Guo, Ce; Xu, Shun; Li, Xin; Han, Cheng
Abstract: Microstructure and nanoindentation properties of the mouthparts for the skillful driller Cyrtotrachelus longimanus are presented. The composition and morphological examinations are made using light, fluorescent, scanning electron microscopy, and Energy Disperse Spectroscopy, respectively. Nanoindentation was carried out to measure the elastic modulus and the hardness of mouthparts. The hardness and modulus for "dry" samples is 0.202 ± 0.065 and 8.604 ± 0.838 GPa, respectively, and the values of "fresh" ones is 0.126 ± 0.0196 and 6.951 ± 0.065 GPa, respectively. These results are critical for analyze the drilling mechanism of the weevil and provide a biological template to inspire the biomimetic design. Abstract : Morphology and chemical composition of the mouthparts in Cyrtotrachelus longimanus was studied. Hardness of "dry" and "fresh" samples is 0.202 ± 0.065 and 0.126 ± 0.0196 GPa, respectively. Modulus of "dry" and "fresh" samples is 8.604 ± 0.838 and 6.951 ± 0.065 GPa, respectively.